Pengamatan Visual Tahap-Tahap Pembentukan Kristal Sistem Eutektikum Asetaminofen-Pseudoefedrin Hidroklorida - Nugrahani, Ilma; Asyarie, Sukmadjaja; Soewandhi, Sundani Nurono; Ibrahim, Slamet (Majalah Ilmu Kefarmasian, 2010)
The aim of this research was to observe the recrystallization process of two component, acetaminophen-pseudoephedrine hydrochloride in ethanol and the thermal profiles. The visual data resulted from polarization microscope observation confirmed with thermograph DSC showed that the crystal habit was represented to the intrinsic character representative by thermodynamic properties of the binary system.The visualization process proved that in different molar ratios, the binary system formed crystals habit with different and step by step showed inhibit, to form polycrystalline until at molar ratio 6:4 formed the fines single crystals mixture which was smaller than before co-recrystallization. Acetaminophen was observed as monoclinic hexagonal crystals while pseudoephedrine hydrochloride was observed monoclinic/orthorombic forms.